1990
DOI: 10.1139/z90-243
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive bionomics of some shallow-water lysianassoids in the Saint Lawrence Estuary, with a review on the fecundity of the Lysianassoidea (Crustacea, Amphipoda)

Abstract: The life history and fecundity of five shallow-water lysianassoids from the Saint Lawrence Estuary were examined. Orchomenella minuta and Or. pinguis are annual and iteroparous (two broods), Psammonyx terranovae is iteroparous (two broods) and probably biennial, and Anonyx sarsi and Onisimus litoralis are biennial and semelparous. Females of A. sarsi and On. litoralis cease feeding on bait shortly before or after oviposition, whereas females of the iteroparous Or. pinguis stop feeding on bait only when broods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
2
19
1
Order By: Relevance
“…Occasionally the gravid females were found with full ovaries with unfertilized oocytes as well, confirming that Orchomenella pinguis is iteroparous as suggested by Sainte-Marie (1990). While the size of the gravid females corresponded to the size of gravid females collected in Saint Lawrence Estuary (Sainte-Marie 1990), the broods were found to be much smaller in the present study.…”
Section: Discussionsupporting
confidence: 85%
“…Occasionally the gravid females were found with full ovaries with unfertilized oocytes as well, confirming that Orchomenella pinguis is iteroparous as suggested by Sainte-Marie (1990). While the size of the gravid females corresponded to the size of gravid females collected in Saint Lawrence Estuary (Sainte-Marie 1990), the broods were found to be much smaller in the present study.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, we identify a 2 yr semelparous life cycle of Onisimus litoralis, well in accordance with earlier studies in the Beaufort Sea (Boudrias & Carey 1988), in the Saint Lawrence Estuary (Sainte-Marie et al 1990) and on Svalbard (Węs8awski et al 2000, Węs8awski & Legeż y?ska 2002. However, our study does not provide any evidence for iteroparity as suggested by Węs8awski et al (2000).…”
Section: Life Strategysupporting
confidence: 91%
“…Only Alicella gigantea and Eurythenes gryllus have been reported to have larger eggs (Sainte-Marie et al 1990), but these are species of a considerably larger size. The brood size is small, but of comparable size to many other lysianassoids (Sainte-Marie et al 1990). However, the lysianassoid species in the genus Anonyx, which are also very common in Adventfjorden, seem to have a different strategy when it comes to reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling with baited traps probably affects the estimates of relative abundance of the different cohorts. The smallest juveniles and ovigerous females are most likely underrepresented, due to different food preferences and a retraction of the gut in ovigerous females (Sainte-Marie et al 1990, Legeżyńska 2008; and males are overrepresented during the mating season (Conlan 1991). Nevertheless, it is possible to detect the different cohorts and thereby to study the life cycle of the species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation